Prevalence and Risk Factors of Tinea Capitis Among School-Aged Children in Bauchi North, Bauchi State, Nigeria (Journal of Pure and Applied Sciences (Science Forum), 2025)
Tinea capitis, a highly contagious fungal infection affecting the scalp and hair shafts, represents a significant public health concern among children, particularly in low- and middle-income countries. Despite its recognized burden, there is limited epidemiological data on its prevalence and determinants in Bauchi North Senatorial District, Nigeria. This study aimed to determine the prevalence of tinea capitis and identify associated risk factors among school-aged children in Bauchi North, Bauchi State. A cross-sectional study was conducted involving 385 children aged 3 to 14 years, selected from primary schools across the region. Scalp and hair samples were collected and analyzed microscopically using potassium hydroxide (KOH) preparations to detect fungal elements. Structured questionnaires were used to obtain sociodemographic and environmental information. Data analysis was performed using SPSS version 23, with Chi-square tests and binary logistic regression employed to assess associations between potential risk factors and tinea capitis infection. The overall prevalence was 31.58%, with males (26.32%) more affected than females (5.26%). The highest infection rate occurred in the 3–5-year age group (14.03%). Statistically significant risk factors included rural residence (OR = 7.600; 95% CI: 3.137–18.410; p < 0.001), low socioeconomic status, poor hygiene practices, overcrowding, and ownership of domestic animals. Protective factors were identified as regular hair washing (OR = 0.307; p < 0.001), frequent visits to barbers or salons (OR = 0.288; p < 0.001), disinfection of grooming tools, and consistent use of soap or shampoo. Clinical symptoms strongly associated with infection included scalp itching, scaling, and patchy hair loss. The findings underscore that tinea capitis remains a prevalent and neglected health issue among children in Bauchi North, fueled by poverty, inadequate hygiene, and environmental exposures. Targeted public health interventions focusing on hygiene promotion, community education, and early treatment are essential to reduce the burden of the disease.